The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/07448481.2015.1117464
|View full text |Cite
|
Sign up to set email alerts
|

In college and in recovery: Reasons for joining a Collegiate Recovery Program

Abstract: Objective Collegiate Recovery Programs (CRPs), a campus-based peer support model for students recovering from substance abuse problems, grew exponentially in the past decade, yet remain unexplored. Methods This mixed methods study examines students’ reasons for CRP enrollment to guide academic institutions and referral sources. Students (N = 486) from the 29 CRPs nationwide operating in 2012 completed an online survey in 2013. Results Students were somewhat older than traditional age (mean age = 26). Now s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…One study has also assessed the motivation of individuals in recovery from SUD to seek PRSS. Wanting to know more about university students participating in peer-based college recovery support services, Laudet et al (2016) surveyed 486 students engaged in 29 college recovery programs across the United States. At the time of survey, students had been abstinent from alcohol and other drugs a mean of 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has also assessed the motivation of individuals in recovery from SUD to seek PRSS. Wanting to know more about university students participating in peer-based college recovery support services, Laudet et al (2016) surveyed 486 students engaged in 29 college recovery programs across the United States. At the time of survey, students had been abstinent from alcohol and other drugs a mean of 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although a strong theoretical case has been made for the potential utility of PRSS in a range of SUD clinical and care settings (e.g., White and Evans, 2014; Laudet et al, 2016), to date PRSS research is limited for specific clinical SUD populations for whom these services are most commonly provided (i.e., those in outpatient, residential and transitional care settings, and recovery community centers). In their 2016 review of the PRSS literature, Bassuk et al noted open questions about the necessary amount and intensity of PRSS interventions, and the optimal contexts for provision of these services and the appropriate skill levels for peers.…”
Section: Discussionmentioning
confidence: 99%
“…Following the national demographics study, Laudet, Harris, Kimball, Winters, and Moberg (2016) analyzed students' reasons for participating in CRPs. This mixed-methods study found the average length of student participation in a CRP was seven academic semesters and revealed students' primary reason for enrolling in a CRP was the desire or need for a supportive peer network.…”
Section: Students In Collegiate Recovery Programsmentioning
confidence: 99%
“…These responses are examples of internal and external methods of maintaining sobriety in this population. Laudet et al stated the importance of building a recovery lifestyle, characterized by healthy behaviors and decision-making [22]. Participants, particularly those involved in WVU CRP, discussed the importance of achieving a healthy lifestyle, which they felt included aspects such as meditation and eating healthily.…”
Section: Chapter Iv: Discussionmentioning
confidence: 99%
“…Mindfulness, which can be defined as a practice that intentionally directs attention to present-moment thoughts and feelings, has been found to increase healthy coping styles among individuals in recovery [18,21]. The use of these types of therapies aim to build recovery lifestyles that have characteristics of healthy functioning and improved quality of life [22].…”
Section: Theory: Sustaining Recovery and Recovery Lifestylesmentioning
confidence: 99%